Letter (copy) : Position of Spanish seamen - Citrine, Walter, 1887-1983
025a-0107-001 Secretary's. WMC/FC/EK/1076. S3/982. 29th April, 1939. Mr. W. J. R. Squance, Associated Society of Locomotive Engineers and Firemen, 9, Arkwright Road, Hampstead, London, N.W.3. Dear Mr. Squance, Position of Spanish Seamen. Many thanks for your letter of the 27th instant enclosing cheque, value £70, which represents your Society's quota for the Spanish Seamen's Maintenance Fund. I have pleasure in enclosing herewith our official receipt for this amount and desire once again to thank your Society for their generous response. Yours sincerely, General Secretary. Receipt. 292/946/25a/107